Penerapan Strategi Pembelajaran Discovery Berbasis Masalah Terhadap Motivasi dan Hasil Belajar - I Nengah Suka Widana; Heron Heron; I Wayan Suana (FPMIPA IKIP PGRI Bali, 2018)
The problem studied is the effect of applying discovery learning strategies based on problems to motivation and biology learning outcomes. The study aims to determine the effect of the application of learning on the motivation and learning outcomes of biology, at Dharma Praja Denpasar High School, 2014-2015 school year. This type of research is a quasi-experimental with a Pre-test Posttest-Only Control Group Design, the population is students of class XI IPA Dharma Praja Denpasar High School consisting of two classes, IPA1 and IPA2, all made into samples (total population). Learning motivation data is obtained by means of motivation questionnaire, and learning outcome data are used learning outcomes test. The data was analyzed using the t-test and MANOVA (via SPSS 22.0 for windows) ts. 5%. The results of the study that the application of problem-based discovery learning strategies affect the motivation and learning outcomes of biology.